Technology Review of Modern Gas Turbine Inlet Filtration Systems. (13th March 2012) - Wilcox, Melissa; Kurz, Rainer; Brun, Klaus
Abstract : An inlet air filtration system is essential for the successful operation of a gas turbine. The filtration system protects the gas turbine from harmful debris in the ambient air, which can lead to issues such as FOD, erosion, fouling, and corrosion. These issues if not addressed will result in a shorter operational life and reduced performance of the gas turbine. Modern day filtration systems are comprised of multiple filtration stages. Each stage is selected based on the local operating environment and the performance goals for the gas turbine. Selection of these systems can be a challenging task. This paper provides a review of the considerations for selecting an inlet filtration system by covering (1) the characteristics of filters and filter systems, (2) a review of the many types of filters, (3) a detailed look at the different environments where the gas turbine can operate, (4) a process for evaluating the site where the gas turbine will be or is installed, and (5) a method to compare various filter system options with life cycle cost analysis.